Which of the following is developed to result in the answer of 1?(1 point)
a.) 5^0+9^0
b.) (−2.97)^0
c.) 13−(7.42)^0
d.) 3(8^0)
10 answers
c.) 13−(7.42)^0
Which of the following shows the correct process of solving −3^0+4.5?(1 point)
To solve the expression −3^0+4.5, we need to evaluate the exponent first, and then perform the addition.
The expression -3^0 means that we have to raise -3 to the power of 0. Any number raised to the power of 0 is always equal to 1. So, -3^0 = 1.
Now, we can rewrite the expression as 1 + 4.5.
Adding 1 and 4.5, we get the final answer:
1 + 4.5 = 5.5
Therefore, the correct process of solving −3^0+4.5 is 5.5.
The expression -3^0 means that we have to raise -3 to the power of 0. Any number raised to the power of 0 is always equal to 1. So, -3^0 = 1.
Now, we can rewrite the expression as 1 + 4.5.
Adding 1 and 4.5, we get the final answer:
1 + 4.5 = 5.5
Therefore, the correct process of solving −3^0+4.5 is 5.5.
Which of the following shows the correct process of solving −3^0+4.5?(1 point)
Responses
−3^0+4.5=−3+4.5=1.5
−3^0+4.5=(−3)^0+4.5=1+4.5=5.5
−3^0+4.5=−3⋅0+4.5=0+4.5=4.5
−3^0+4.5=−1⋅3^0+4.5=−1⋅1+4.5=−1+4.5=3.5
Responses
−3^0+4.5=−3+4.5=1.5
−3^0+4.5=(−3)^0+4.5=1+4.5=5.5
−3^0+4.5=−3⋅0+4.5=0+4.5=4.5
−3^0+4.5=−1⋅3^0+4.5=−1⋅1+4.5=−1+4.5=3.5
The correct process of solving −3^0+4.5 is:
−3^0+4.5=(−3)^0+4.5=1+4.5=5.5
So the correct option is:
−3^0+4.5=(−3)^0+4.5=1+4.5=5.5
−3^0+4.5=(−3)^0+4.5=1+4.5=5.5
So the correct option is:
−3^0+4.5=(−3)^0+4.5=1+4.5=5.5
Which of the following is an equivalent expression to 7/(−5.3)^0+4⋅9 when applying the Zero Power Rule? (1 point)
7/5.3+4⋅9
7/0+4⋅9
7/5.3^0+36
7/1+4⋅9
7/5.3+4⋅9
7/0+4⋅9
7/5.3^0+36
7/1+4⋅9
The Zero Power Rule states that any non-zero number raised to the power of 0 is equal to 1. Therefore, when applying the Zero Power Rule to the expression 7/(−5.3)^0+4⋅9, we can simplify it to:
7/1+4⋅9
So, the equivalent expression is:
7/1+4⋅9
7/1+4⋅9
So, the equivalent expression is:
7/1+4⋅9
you got all but one wrong
I apologize for the incorrect answer. Let's try again.
When applying the Zero Power Rule, any non-zero number raised to the power of 0 is equal to 1. Therefore, the expression 7/(−5.3)^0 can be simplified as 7/1.
So, the equivalent expression to 7/(−5.3)^0+4⋅9 when applying the Zero Power Rule is:
7/1 + 4⋅9
Thus, the correct option is:
7/1 + 4⋅9
When applying the Zero Power Rule, any non-zero number raised to the power of 0 is equal to 1. Therefore, the expression 7/(−5.3)^0 can be simplified as 7/1.
So, the equivalent expression to 7/(−5.3)^0+4⋅9 when applying the Zero Power Rule is:
7/1 + 4⋅9
Thus, the correct option is:
7/1 + 4⋅9
Which of the following is an equivalent expression to 12(9−70)+(−29)0? (1 point)
Responses
12(9−1)−1
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 1 right parenthesis minus 1
12(2)+1
Start Fraction 1 over 2 End Fraction left parenthesis 2 right parenthesis plus 1
12(9−1)+1
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 1 right parenthesis plus 1
12(9−0)+0
Responses
12(9−1)−1
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 1 right parenthesis minus 1
12(2)+1
Start Fraction 1 over 2 End Fraction left parenthesis 2 right parenthesis plus 1
12(9−1)+1
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 1 right parenthesis plus 1
12(9−0)+0